Afro-Ecuadorian women: Voices of resistance in the struggle for the recognition of their rights - Siguenza-Orellana, Sonia Catalina (2024)
Afro-descendant women, as a result of the intersectionality of gender, class and ethnicity, face difficulties in the full exercise of their human rights. In this context, the participation and strategies of Afro-descendant women in the process of formulating their movement's demands in Ecuador are analyzed. For this purpose, a qualitative-narrative approach is applied, based on the epistemological principles of hermeneutics. Through the technique of the semi-structured interview, applied to a politically important sample that allowed to explore, in depth, the subject. The results show that women are the leaders of the organizations, educators, guardians of ancestral knowledge and caretakers of community life. Their participation in the formulation of demands does not guarantee their representation in feminist movements, and they must propose their own agendas and strategies within the social movement to ensure that their voices are heard, and their demands are represented. Their main achievement is their recognition as a people in the 2008 Constitution, however, this progress has not translated into tangible improvements. Concluding that, despite the importance of their roles, strategies and participation in the formulation of their demands, these are not fully integrated and prioritized in the political and social agendas.